DEVELOPMENT OF FAST-DISSOLVING TABLETS OF AMLODIPINE BESYLATE BY SOLID DISPERSION TECHNOLOGY USING POLOXAMER 407 AND POLOXAMER 188 - V, Manimaran; N, Damodharan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Amlodipine besylate is a calcium channel blocker used in the treatment of hypertension which is practically insoluble in water. The present study aims to design oral fast-release tablets of amlodipine besylate and to optimize the dissolution of the drug by altering the carrier concentration. Materials and Methods: Poloxamer 407 (P407) and poloxamer 188 (P188) were selected as carriers for the preparation of solid dispersion (SD) by the solvent evaporation method with different drug-polymer ratios. The prepared SDs were evaluated for the physical state, drug:carrier interactions by X-ray diffraction (XRD), infrared spectroscopy, differential scanning calorimetry, and scanning electron microscopy. Results: From the dissolution studies, it is confirmed that all SDs showed increased dissolution rate when compared to pure amlodipine besylate. Among the two polymers used, P407 was found to be better than P188 in enhancing dissolution efficiency. The tablets were prepared using SD of amlodipine besylate containing P407 as a carrier. The results showed that P407 SD-based tablets gave a significantly higher release of amlodipine besylate when compared with control tablets. The infrared spectral studies showed that there was no significant interaction between amlodipine besylate and its formulation with different polymers used in the preparation of SDs. XRD studies revealed that the degree of crystallinity of amlodipine besylate reduced when the concentration of carriers increased, which reveals that the drug is in amorphous nature. Conclusion: The combination of SD technology and using superdisintegrants in the formulation is a promising approach for preparing efficient, fast-dissolving tablet of poorly water-soluble drugs, viz., amlodipine besylate.